The Effect of Provision of Chicken Manure and Local Micro-Organisms of Bamboo Shoots on the Growth and Yield of Chickpeas (Phaseolus vulgaris L.) in Red Yellow Podsolic Soil - Agus Suyanto; Agnes Tutik Purwani Irianti; Rini Suryani (STKIP Singkawang, 2022)
This study aimed to determine the effect of the interaction of chicken manure and Local Micro-Organisms (MOL) on bamboo shoots on the growth and yield of chickpeas in Red Yellow Podsolic soil. This study used a randomized block design (RAK) with a factorial pattern consisting of two treatment factors, namely the first factor was the dose of chicken manure with 3 treatment levels (a), namely: a1= Dose of chicken manure 1.2 kg/ plot (10 tons/ha), a2= Dose of Chicken Manure 1.8 kg/plot (15 tons/ha), a3= Dose of Chicken Manure 2.4 kg/plot (20 tons/ha), second factor was MOL concentration bamboo shoots with 3 treatment levels, namely: m1= giving MOL 0.0125%, m2= giving MOL 0.025 %, m3= giving MOL 0.0375%. So there are 9 treatment combinations, namely a1m1, a1m2, a1m3, a2m1, a2m2, a2m3, a3m1, a3m2, and a3m3. Based on the results of the study showed that treatment with chicken manure had a very significant effect on the variable number of branches, the number of pods per plant, weight of pods per plant, weight of pods per plot, and significantly affected the variables of plant height and number of pods per plot. The MOL treatment of bamboo shoots had a very significant effect on the variables of plant height, pod weight per plant, and had a significant effect on the variables of number of branches, number of pods per plant, number of pods per plot, and weight of pods per plot. The interaction of giving chicken manure and MOL of bamboo shoots had no significant effect on all observed variables. Treatment levels A3 and M3 gave the best results on plant height variables 531.00 cm, number of branches 4.00 branches, number of pods/plant 36.00 pods, number of pods per plot 264.00 pods, pods/plant weight 248.67 g, pod weight per plot 2.92 kg.